Analysis and Design of Data Warehouse on Academic STMIK STIKOM Bali - Komang Budiarta; Putu Agung Ananta Wijaya; Cokorde Gede Indra Partha (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2017)
College accreditation by BAN-PT is one of the parameters in determining the quality of universities in Indonesia. As consideration to achieve the standard from BAN-PT, so they have an evaluation process itself in study program or college to be meet the standard universities when set by the BAN-PT. In carrying out the process of self evaluation, required data source that is used as the basis in assessing on a criteria. In most of the study program, all data spread on the system information and physical document that different, that is require more time and effort to integrate up to interpret. Data warehouse fight important in collecting data that spread and become an information. The process data warehouse with ETL used to integrate, extract, clean, transforming and reload into the data warehouse. With the existence of the data warehouse on Academic STIMIK STIKOM Bali can make it easier for executives to get the information to support the standard accreditation standart three and can be used as a reference in decision making.